Description of the embryonic development of Holothuria floridana (Pourtalès, 1851) to produce juveniles for aquaculture and restocking - Libni A. Maas-Hernández; Miguel A. Olvera-Novoa; Arlenie Rogers; Luis Felaco; Karina Macal-López; Teresa Colás-Marrufo (PLoS ONE, 2025)
Overexploitation has severely affected the populations of Holothuria floridana, the second most valuable species of sea cucumber in the Gulf of Mexico and Greater Caribbean. Knowledge about its reproductive biology is limited, so this study aimed to update particularities about its reproduction and embryonic development that supports aquaculture technologies. Adults were collected in coastal waters off Celestún, Yucatán, Mexico, and transferred to the laboratory to induce spawning by thermal shock. Oocytes were obtained from individual females and fertilized artificially. Samples were incubated under controlled conditions to assess embryonic development using standard histology and by applying optical and scanning electron microscopy techniques. Fertilized oocytes settle and adhere to the substrate through a gelatinous cover. This species exhibits a lecithotrophic embryonic development, with a non-ciliated vitellaria larva that does not go through the auricularia and doliolaria stages, hatching as pentactula. At 1.5 dpf, the primordia of the oral tentacles appeared; for the 2 dpf, the structures of the oral tentacles were apparent, and a primary intestinal tubule was also distinguished, with a link with the anus at 3 dpf when the ring canal of the water vascular system appeared. At 3.5 dpf, the intestinal tubule enlarged and took on a rounded shape, hatching as a pentactula at 4 dpf, with the intestine connected to the mouth and anus, confirming that the digestive tube is complete and functional at this stage showing feeding behavior. The early juvenile stage was attained between 5 and 7 dpf, a much shorter time when compared with planktotrophic species. Its direct embryonic development, the absence of planktotrophic larvae, and the feasibility of inducing spawning through thermal shocks conferred H. floridana high potential for aquaculture in the Tropical Western Atlantic. Considering its benthic development, these results give practical information for developing hatchery infrastructure and protocols for rearing in captivity.